Capacity of the bovine intestinal mucus and its components to support growth of Escherichia coli O157:H7 - C.C. Aperce (Animal, 2014)
Colonization of the gastrointestinal tract of cattle by Shiga toxin-producing Escherichia coli increases the risk of contamination of food products at slaughter. Our study aimed to shed more light on the mechanisms used by E. coli O157:H7 to thrive and compete with other bacteria in the gastrointestinal tract of cattle. We evaluated, in vitro, bovine intestinal mucus and its constituents in terms of their capacity to support growth of E. coli O157:H7 in presence or absence of fecal inoculum, with and without various enzymes. Growth of E. coli O157:H7 and total anaerobic bacteria were proportionate to the amount of mucus added as substrate. Growth of E. coli O157:H7 was similar for small and large intestinal mucus as substrate, and was partially inhibited with addition of fecal inoculum to cultures, presumably due to competition from other organisms. Whole mucus stimulated growth to the greatest degree compared with other compounds evaluated, but the pathogen was capable of utilizing all substrates to some extent. Addition of enzymes to cultures failed to impact growth of E. coli O157:H7 except for neuraminidase, which resulted in greater growth of E. coli O157 when combined with sialic acid as substrate. In conclusion, E. coli O157 has capacity to utilize small or large intestinal mucus, and growth is greatest with whole mucus compared with individual mucus components. There are two possible explanations for these findings (i) multiple substrates are needed to optimize growth, or alternatively, (ii) a component of mucus not evaluated in this experiment is a key ingredient for optimal growth of E. coli O157:H7.